KAJIAN TEOLOGIS YOHANES 10:1-18 MEMBENTUK ULANG KONSEP GEMBALA SEBAGAI TELADAN - Manuel Marto Pasau; Doni Heryanto; Daud Manno (Phronesis: Jurnal Teologi dan Misi, 2023)
The call to be a pastor in the post-truth era has resulted in the birth of church leaders who lack competence. This problem is challenging for the church to rethink what a true shepherd looks like. This research examines a very famous metaphor from John chapter 10:1-18. It describes how a good shepherd is a characteristic every church leader must have. This research provides three profiles of a good shepherd: content, character, and competence. These three values make a pastor an impactful leader. Here, pastors need to be seen as others who are present as role models, not just leaders with various functions and characters. By studying theology, it is necessary to understand pastors in the current context.